2009
DOI: 10.1523/jneurosci.1248-09.2009
|View full text |Cite
|
Sign up to set email alerts
|

A Neuroligin-4 Missense Mutation Associated with Autism Impairs Neuroligin-4 Folding and Endoplasmic Reticulum Export

Abstract: Neuroligins (NLs) are postsynaptic cell-adhesion molecules essential for normal synapse function. Mutations in neuroligin-4 (NL4; gene symbol: NLGN4) have been reported in some patients with autism spectrum disorder (ASD) and other neurodevelopmental impairments. However, the low frequency of NL4 mutations, and the limited information about the affected patients and the functional consequences of their mutations, cast doubt on the causal role of NL4 mutations in these disorders. Here, we describe two brothers … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
174
0
4

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 170 publications
(190 citation statements)
references
References 55 publications
10
174
0
4
Order By: Relevance
“…Remarkably, mutations in Nlgn3/4 are involved in autism spectrum disorders (ASDs) which have been shown to destabilize the Nrxns-Nlgns complexes (Arac et al 2007;Chen et al 2008). In addition, a retention of Nlgns in the endoplasmic reticulum as well as a decrease in its affinity for Nrxns have been associated with some of those mutations (Comoletti et al 2004;Zhang et al 2009), suggesting that impaired trafficking and protein binding properties of Nrxns-Nlgns might be related to the disease.…”
Section: Introductionmentioning
confidence: 99%
“…Remarkably, mutations in Nlgn3/4 are involved in autism spectrum disorders (ASDs) which have been shown to destabilize the Nrxns-Nlgns complexes (Arac et al 2007;Chen et al 2008). In addition, a retention of Nlgns in the endoplasmic reticulum as well as a decrease in its affinity for Nrxns have been associated with some of those mutations (Comoletti et al 2004;Zhang et al 2009), suggesting that impaired trafficking and protein binding properties of Nrxns-Nlgns might be related to the disease.…”
Section: Introductionmentioning
confidence: 99%
“…Vectors expressing a soluble IgG‐NX1β fusion protein (in a pCMV5 backbone) were provided by Professor Thomas C. Südhof (Zhang et al., 2009). …”
Section: Methodsmentioning
confidence: 99%
“…In vitro and in vivo experiments have indicated that the autism‐related neuroligin mutations may affect synapse maturation and function. (Bemben et al., 2015; Chih et al., 2004; Ey, Leblond, & Bourgeron, 2011; Jaramillo, Liu, Pettersen, Birnbaum, & Powell, 2014; Zhang et al., 2009). …”
Section: Introductionmentioning
confidence: 99%
“…Multiple genetic changes in Nrxn [84][85][86][87][88][89][90][91][92][93][94] and Nlgn genes [92,93,[95][96][97][98][99][100][101][102][103][104][105][106][107][108][109][110] have been found in ASD patients. These changes include (i) point mutations, which cause frame shifts, small deletions, and missense mutations in both coding and promoter regions, (ii) distinct translocation events, and (iii) large-scale deletions of chromosomal DNA containing these gene loci.…”
Section: Neurexins and Neuroliginsmentioning
confidence: 99%